(untitled) (Orfeu, 2020)
An immediate association is usually established between the proclaimed “influence of jazz” and the emergence and consolidation of Bossa Nova. This paper, however, travels in time with the intention of documenting analytically how representation struggles between, on the one hand, sectors revering tradition and Brazilianness and, on the other, those presenting themselves as modernizing date back from before that era. To this end, the author proposes an overview of the post WW1 period to spot the rise of jazz bands, which, in the “jazz age” (the 1920s), extended their reach to different areas across Brazil, including inland cities. On their rising trajectory, American musical elements continued to seep in, especially during the 1930s, when fox trot became the foreign music genre with the highest number of recordings in the country. In order to highlight this phenomenon, this article intends to capture the reactions to what was understood as a process of denationalization of Brazilian popular music, which would eventually pave the way to the “disfigurement” of “authentic” samba carried out by samba-canção and Bossa Nova.